Acoustic Emission Response to Severe Friction in Deformation by Cutting on Metals and Alloys; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Shamarin N. N. Nikolay Nikolaevich; Filippov A. V. Andrey Vladimirovich; Tarasov S. Yu. Sergei Yulievich; Filippova E. O. Ekaterina Olegovna; Vorontsov A. V. (2018, 2018)
Title screen